2015
DOI: 10.1063/1.4927127
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of integration constants and various plasma parameters on the dynamics of the soliton in different physical plasmas

Abstract: The nonlinear dynamics and propagation of ion acoustic waves in a relativistic and ideal plasmas, which have the pressure variation of electrons and ions and degenerate electrons, are investigated using the analytic solution of KdV type equations performed applying (G′/G)-expansion and (G′/G,1/G)-expansion methods. The effects of various parameters, such as phase velocity of the ion acoustic wave, the ratio of ion temperature to electron temperature, normalized speed of light, electron and ion streaming veloci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…Nonlinear partial differential equations (NPDEs) are consequences of the mathematical models of problems arising in various fields of science. Among these equations, KdV and KdV typed equations can be applied to many important applications in physics and other fields of science . In order to provide a better understanding of the integrable systems, Wazwaz, in his article, used an integrable nonlinear KdV equation by combining the KdV recursion operator and the negative‐order recursion operator, uxt+uxxxx+uxxxt+6uxxux+4uxuxt+2uxxut=0, where u = u ( x , t ).…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear partial differential equations (NPDEs) are consequences of the mathematical models of problems arising in various fields of science. Among these equations, KdV and KdV typed equations can be applied to many important applications in physics and other fields of science . In order to provide a better understanding of the integrable systems, Wazwaz, in his article, used an integrable nonlinear KdV equation by combining the KdV recursion operator and the negative‐order recursion operator, uxt+uxxxx+uxxxt+6uxxux+4uxuxt+2uxxut=0, where u = u ( x , t ).…”
Section: Introductionmentioning
confidence: 99%
“…As a pioneer work Li et al [15] has applied the two-variable (G ′ /G, 1/G)-expansion method and found the exact solutions of Zakharov equations. Some applications of the (G ′ /G, 1/G)-expansion method can be seen in [16,17,18,19,20]. (1/G ′ )-expansion method introduced by Yokus [21] firstly.…”
Section: Introductionmentioning
confidence: 99%
“…The original (G /G)-expansion method is generalized to find (G /G, 1/G)-expansion method [13]. Some applications of (G /G)-expansion method can be seen in [14][15][16][17][18]. As a pioneer work [19] has applied the two-variable (G /G, 1/G)-expansion method and found the exact solutions of Zakharov equations.…”
Section: Introductionmentioning
confidence: 99%